Net Community Production (NCP), photosynthesis, and respiration measured in Georgia estuaries using in situ samples with the PIGI (Pressure of In-situ Gas Instrument) system - Benjamin Lowin; Sara Rivero-Calle (PANGAEA, 2025)
The PIGI dataset includes continuous dissolved oxygen and associated physical parameters (temperature, salinity, etc.) collected from a floating dock on the Wilmington River (31.9624°N 81.0122°W). Data collection occurred in June, September and December of 2024. The has a temporal resolution of 10 seconds. NCP was calculated following Izett and Tortell (2020), from in situ oxygen and nitrogen gas data supporting meteorological measurements. Minor updated to the above-mentioned method are explained in the related manuscript. Data are provided in tabular format and include time, latitude, longitude, depth, and derived fluxes.
In: Lowin, B; Rivero-Calle, S (2025): Net Community Production (NCP), photosynthesis, and respiration measured in Georgia estuaries using two complementary methods [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983807